Alkaline Peptone Water-Based Enrichment Method for mcr-3 From Acute Diarrheic Outpatient Gut Samples - Sun, Qiaoling; Hu, Yanyan; Zhou, Hongwei; Shu, Lingbin; Wang, Hanyu; Huang, Zixian; Zhang, Rong (Frontiers in Medicine, 2018)
A third plasmid-mediated colistin resistance gene, mcr-3, is increasingly being reported in Enterobacteriaceae and Aeromonas spp. from animals and humans. To investigate the molecular epidemiology of mcr in the gut flora of Chinese outpatients, 152 stool specimens were randomly collected from outpatients in our hospital from May to June, 2017. Stool specimens enriched in alkaline peptone water or LB broth were screened for mcr-1, mcr-2, and mcr-3 using polymerase chain reaction (PCR)-based assays. Overall, 19.1% (29/152) and 5.3% (8/152) of the stool samples enriched in alkaline peptone water were PCR-positive for mcr-1 and mcr-3, respectively, while 2.7% (4/152) of samples were positive for both mcr-1 and mcr-3. Strains isolated from the samples that were both mcr-1- and mcr-3-positive were subjected to antimicrobial susceptibility testing by broth microdilution. They were also screened for the presence of other resistance genes by PCR, while multilocus sequence typing and whole genome sequencing were used to investigate the molecular epidemiology and genetic environment, respectively, of the resistance genes. mcr-3-positive Aeromonas veronii strain 126-14, containing a mcr-3.8-mcr-3-like2 segment, and mcr-1-positive Escherichia coli strain 126-1, belonging to sequence type 1485, were isolated from the sample from a diarrheic butcher with no history of colistin treatment. A. veronii 126-14 had a colistin minimum inhibitory concentration (MIC) of 2 μg/mL and was susceptible to antibiotics in common use, while E. coli 126-1 produced TEM-1, CTX-M-55, and CTX-M-14 β-lactamases and was resistant to colistin, ceftazidime, and cefotaxime. Overall, there was a higher detection rate of mcr-3-carrying strains with low colistin MICs from the samples enriched in alkaline peptone water than from samples grown in LB broth.